2018
DOI: 10.1002/mrm.27152
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved contrast‐enhanced MR angiography with single‐echo Dixon fat suppression

Abstract: Time-resolved contrast-enhanced MRI with single-echo Dixon fat suppression shows high image quality, improved vessel delineation, and reduced sensitivity to motion when compared to time-subtraction methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Moreover, the study has confirmed that the detection rate of CEUS combined with enhanced MR scanning was higher. The detection rate of lesions, localization accuracy, qualitative accuracy, and diagnostic coincidence rate in the experimental group are significantly better than those in the control group, which was similar to the results of [ 18 ]. Our results indicated that CEUS combined with enhanced MR scanning was more accurate and comprehensive in the diagnosis and differentiation of ICC.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the study has confirmed that the detection rate of CEUS combined with enhanced MR scanning was higher. The detection rate of lesions, localization accuracy, qualitative accuracy, and diagnostic coincidence rate in the experimental group are significantly better than those in the control group, which was similar to the results of [ 18 ]. Our results indicated that CEUS combined with enhanced MR scanning was more accurate and comprehensive in the diagnosis and differentiation of ICC.…”
Section: Discussionsupporting
confidence: 87%
“…In a small pilot study of 8 healthy volunteers, Nezafat et al demonstrated significantly higher CNR and SNR in the coronary artery tree with Dixon water-fat separation than spectral presaturation with inversion recovery (SPIR) fat suppression at 3 T, even without IV contrast administration [33]. mDixon techniques have been proven useful in peripheral CMRA as well [38, 39]. In contrast, Börnert et al, found that SNR and CNR tended to drop in bSSFP sequences after gadolinium administration and suggested that fat-saturated images may be advantageous in demonstrating small epicardial vessel structures and tissue boundaries [20].…”
Section: Discussionmentioning
confidence: 99%